2005
DOI: 10.1007/s00392-005-0199-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management of oral Anticoagulation in nonvalvular Atrial Fibrillation (SMAAF study)

Abstract: Management of oral anticoagulation by INR self-management in patients with atrial fibrillation is not inferior to conventional care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 29 publications
0
48
0
2
Order By: Relevance
“…59 Similarly, one trial was discontinued before the end of the prespecified follow-up due to difficulties in the recruitment process. 60 Overall, only four trials were assessed to have adequate sequence generation, concealed allocation and blinded outcome assessment and, therefore, were judged at low risk of bias. …”
Section: Coaguchek Xs Versus Coaguchek Smentioning
confidence: 99%
See 3 more Smart Citations
“…59 Similarly, one trial was discontinued before the end of the prespecified follow-up due to difficulties in the recruitment process. 60 Overall, only four trials were assessed to have adequate sequence generation, concealed allocation and blinded outcome assessment and, therefore, were judged at low risk of bias. …”
Section: Coaguchek Xs Versus Coaguchek Smentioning
confidence: 99%
“…55,57,[61][62][63][64][65] In 11 trials, the randomisation process proved to be adequate but no information was provided on the way in which participants were allocated to the study interventions. 58,60,[66][67][68][69][70][71][72][73][74] One trial 75 reported adequate details about the generation of the random sequence but failed to conceal the allocation of participants to study interventions. In contrast, another trial 76 reported adequate information on allocation concealment but failed to provide details on the randomisation process.…”
Section: Selection Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Several published trials have compared self-management with physician management or management in an anticoagulation clinic. [4][5][6][7][8][9][10][11][12][13] It has been found that patients who self-manage check their INR more frequently and are able to maintain a greater proportion of INRs within the therapeutic range compared with those whose therapy is monitored by a physician or in an anticoagulation clinic. [11][12][13] The results of a recent meta-analysis showed a significant reduction in thromboembolic events (odds ratio [OR] 0.45), major hemorrhagic events (OR 0.65) and all-cause mortality (OR 0.61) for those using a self-management or self-test strategy.…”
mentioning
confidence: 99%